Knowledge of and Attitude on Assessment of Substance Use disorders of Nurses Working in General Wards - Sumity Arora Tarafdar; Sandhya Gupta (Indian Journal of Psychiatric Nursing)
Early detection of substance abuse disorders can facilitate treatment. Health care professional's knowledge and attitudes can play a role in the failure to identify and address patients with substance use problems and may negatively influence the care that these patients receive. The objectives of the study were to assess the knowledge of nurses working in general wards regarding assessment of substance abuse in patients and their attitude towards patients withsubstance abuse. Method: A cross sectional study was conducted on 150 Nurses working in medical, surgical, emergency, ICU, pediatrics, obstetrics and gynecology wards of selected hospital of New Delhi, selected by simple random sampling method. A socio-demographic data was collected. Other Tools: A structured knowledge questionnaire and Attitude scale was used for assessing knowledge and attitude. Total knowledge score ranged from 0-16 and total attitude score ranged from0-75. Informed consent was taken prior to the data collection from the study subjects. Results: Mean knowledge score of subjects regarding substance use was 7.17 (with range of score as 1-13). One third of the subjects 32% (n=48) have inadequate knowledge, 58.66% (n=88) have average knowledge and 9.33% (n=44) have good knowledge regarding assessment of substance use disorder in patients. The unfavorable attitude was shown by 5.33% (n=8) of subjects and 94.66% (n=148) of subjects have favorable attitude towards patients with substance use disorders. Knowledge was significantly associated with attitude. The was no association of knowledge and attitude with selected demographic variable. Conclusion: The study findings suggest that majority of nurses need to attend educational and training programs for assessment of substance use disorders to participate in care planning of persons with substance use disorders.